Comparing Spatio-Temporal Dynamics of Functional and Taxonomic Diversity of Phytoplankton Community in Tropical Cascading Reservoirs - Resende, Nathália da Silva; Santos, Juliana Barreto Oliveira dos; Josué, Iollanda Ivanov Pereira; Barros, Nathan Oliveira; Cardoso, Simone Jaqueline (Frontiers in Environmental Science, 2022)
Small Hydroelectric Power Plants (SHPs) are considered hydroelectric plants of reduced size and power that modify the landscape in a lower degree. As they are generally built in sequence along the course of a river, these reservoirs are subject to the Cascading Reservoir Continuum Concept (CRCC), which provides a gradient effect mainly on suspended particles and nutrients. These changes can be observed in the phytoplankton community, which respond in terms of structure and function to environmental changes. Here, we aimed to investigate whether spatial variation would be more explanatory than temporal variation for phytoplankton structure and composition in cascade reservoirs. Furthermore, we sought to understand the effect of the hydrodynamics of run-of-river and storage reservoirs for phytoplankton community composition. The study was carried out over 6 years in three small hydroelectric power plants located on the Paraibuna River, Brazil, totaling 24 campaigns. After counting and identification, the phytoplankton species were classified according to qualitative functional traits related to morphology, physiology, and behavior. The reservoirs presented significant differences for nutrients and suspended solids, corroborating with the CRCC. Nonetheless, these variables were not able to explain the distribution of phytoplanktonic species. Changes in taxonomic and functional composition were observed mainly related to reservoir hydrodynamics. However, the temporal variation observed in the three reservoirs also proved to be an important factor for the community structure. The last reservoir in the cascade was the one with the greatest diversity of phytoplankton species and functional diversity. In addition, the taxonomic and functional diversity indices were positively correlated. Despite this outcome, in our study it did not indicate that taxonomic diversity was a good predictor of functional diversity, since at a certain point, functional richness reached a plateau. Here we highlight the complexity of understanding the role of cascading reservoirs in the structure and function of phytoplanktonic communities since cascading reservoirs, even within the same stretch of river, are subject to large spatial and temporal variations.